Aktivitas Nitrogenase, Serapan Hara dan Pertumbuhan Dua Varietas Kedelai pada Kondisi Jenuh Air dan Kering - Munif Ghulamahdi; Sandra Arifin Aziz; Maya Melati; Nurwita Dewi; Sri Astuti Rais (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2006)
The objective of this experiment was to study nitrogenase activity, nutrient uptake, and growth of two soybean varieties under saturated and dry soil conditions. The experiment was conducted in the plastic house at IPB Experimental Station, Babakan Sawah, Bogor, from August to November 2001. The experiment used the complete randomized design with four replications. The first factor was variety, consisted of Wilis and Bromo. The second factor was water condition, consisted of continuous saturated, saturated-dry, and dry conditions. Wilis and Bromo were not significantly different in nitrogenase activity; P and K uptake; nodule, stalk, leaf, pod, and seed dry weight. Wilis and Bromo were significantly different in root dry weight and leaf N uptake at 3 weeks after planting. Root dry weight and leaf N uptake of Wilis was lower than those of Bromo.The levels of nitrogenase activity, nutrient uptake, and plant weight under different water conditions were in the following order, from low to high, dry, saturated-dry, continuous. Under continuous saturated condition, nitrogenase activity, N uptake, P uptake, K uptake, nodule, root, stalk, leaf, and pod dry weight were 6800 %, 265 %, 320 %, 288 %, 1386 %, 362 %, 289 %, 265 %, 329 % of those under dry condition, respectively at 9 weeks after planting. Key words: Soybean, saturated culture, dry culture, nitrogenase activity, nutrient uptake